2022
DOI: 10.1136/bmjopen-2021-049175
|View full text |Cite
|
Sign up to set email alerts
|

HIV testing behaviour and associated factors in men who have sex with men by level of urbanisation: a cross-sectional study in the Netherlands

Abstract: ObjectivesRegular HIV testing in men who have sex with men (MSM) enables timely entry into care and reduces the likelihood of HIV transmission. We aimed to assess HIV-testing behaviour and associated factors in MSM by urbanisation of place of residence.DesignData were derived from online survey (‘Men & Sexuality’) in the Netherlands, which was mainly advertised on social media (Facebook and Instagram), dating websites, apps for MSM (Grindr and PlanetRomeo) and gay media.Primary and secondary outcome measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 30 publications
3
7
0
Order By: Relevance
“…Local stakeholder networks, community based organizations and local communities can be engaged to maximize access to information (for all) and access to PPV (for those at highest risk). Respondents who lacked connectedness to the gay/queer community were less likely to want PPV, in line with research findings on HIV testing and COVID-19 testing uptake ( 28 , 29 ). Disconnected people are also known to less engage in preventive healthcare.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Local stakeholder networks, community based organizations and local communities can be engaged to maximize access to information (for all) and access to PPV (for those at highest risk). Respondents who lacked connectedness to the gay/queer community were less likely to want PPV, in line with research findings on HIV testing and COVID-19 testing uptake ( 28 , 29 ). Disconnected people are also known to less engage in preventive healthcare.…”
Section: Discussionsupporting
confidence: 82%
“…Those who live in less urbanized areas and those who lack connection to a gay/queer community might benefit from strengthened public health efforts tailored to their context. Disparities by urbanization level in mpox PPV uptake and in other mpox mitigation strategies were demonstrated in two US studies ( 26 , 27 ), and were also observed in HIV testing uptake ( 28 ). Local stakeholder networks, community based organizations and local communities can be engaged to maximize access to information (for all) and access to PPV (for those at highest risk).…”
Section: Discussionmentioning
confidence: 83%
“…Public health efforts should be strengthened in less urbanized areas together with local stakeholder networks, community based organizations and local communities. Furthermore, respondents who lacked connectedness to the gay/queer community were less likely to want PPV, in line research findings on HIV testing and COVID-19 testing uptake [27,28]. Disconnected people are also known to less engage in preventive healthcare.…”
Section: Discussionsupporting
confidence: 63%
“…Subgroups less likely to want vaccination were defined by were they were born and live (born in the Netherlands, live in lower urbanized areas), their social networks (no MPX-vaccinated social network members, lack of connection to the gay/queer community), and by their sexual behavior (at most one recent partner). Disparities by urbanization level in MPX prevention behavior (PPV uptake and other MPX mitigation strategies) were demonstrated in two US studies [25,26], and was also observed in HIV testing uptake [27]. Public health efforts should be strengthened in less urbanized areas together with local stakeholder networks, community based organizations and local communities.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that access to sexual health care during the COVID-19 pandemic within the Netherlands was unevenly distributed, for example between urban and rural areas [ 24 ]. A recent spatial analysis found greater PrEP use in the main urban areas of the Netherlands (Amsterdam, Utrecht, Leiden, the Hague, and Rotterdam) compared to the rest of the country before the pandemic [ 25 ].…”
Section: The Dutch Contextmentioning
confidence: 99%